2010
DOI: 10.3390/medicina46070065
|View full text |Cite
|
Sign up to set email alerts
|

De novo erosive esophagitis in duodenal ulcer patients related to pre-existing reflux symptoms, smoking, and patient age, but not to Helicobacter pylori eradication: a one-year follow-up study

Abstract: It remains unclear whether the Helicobacter pylori eradication may cause or provoke gastroesophageal reflux disease. Therefore, we aimed to elucidate the role of H. pylori eradication and other factors in the development of erosive esophagitis in patients with duodenal ulcer. Materials and methods. We enrolled 183 H. pylori-positive duodenal ulcer patients without erosive esophagitis. Final endoscopy was performed 12 months later or in case if ulcer relapse was suspected. H. pylori was diagnosed by the urease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Of these, 15 studies met the exclusion criteria (retrospective study design, single arm study, abstract only, and duplicated study) and eight were reviews, which were excluded. Finally, 27 full articles were assessed for eligibility ( Figure 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. On categorization, 12 studies were assigned to Category A [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], 10 to Category B [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], and 5 to Category C [ 29 , 30 , 31 , 32 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 15 studies met the exclusion criteria (retrospective study design, single arm study, abstract only, and duplicated study) and eight were reviews, which were excluded. Finally, 27 full articles were assessed for eligibility ( Figure 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. On categorization, 12 studies were assigned to Category A [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], 10 to Category B [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], and 5 to Category C [ 29 , 30 , 31 , 32 ,…”
Section: Resultsmentioning
confidence: 99%
“…We divided the studies into three categories: Category A were studies that compared the incidence rates of reflux esophagitis and reflux-related symptoms between patients receiving H. pylori eradication therapy (case) or placebo (control); Category B were studies that compared patients with successful eradication (case) or eradication failure and receipt of placebo (control, infection persisted); and Category C were studies that compared patients with successful eradication therapy (case) or eradication failure, receipt of placebo, and no-receipt of drug/placebo (control, infection persisted) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Author names, publication year, country where the study was conducted, follow-up period, number of patients, smoking habit, alcohol use, sex, age, eradication regimen, eradication rate, and incidence rates of endoscopic reflux esophagitis and reflux-related symptoms, such as heart burn, discomfort, and chest pain, before and after treatment were extracted from each study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CagA + strains induce more extensive epithelial cell injuries [69,72] and secrete more proinflammatory cytokines (such as interleukin-8) [69,73] with more intense infiltration of the gastric mucosa by neutrophils and mononuclear cells [72,74] and more rapid development of atrophic gastritis [75] and concomitant changes in gastric secretion [70]. Using visualized images of Congo red chromoendoscopy, Sekine et al [76] found lnoue et al [42] Kim et al [43] Levine et al [44] Malfertheiner et al [10] McColl et al [45] Murai et al [46] Take et al [15] Tsukada et al [47] Total (95% CI) Bytzer et al [49] Hamada et al [14] Harvey et al [51] Jonaitis et al [52] Kim et al [54] Malfertheiner et al [10] Moayyedi et al [53] Nam et al [55] Ott et al [50] Vakil et al [11] Wu et al [56] Total (95% CI) that the acid-secreting mucosa in the fundus expanded in most cases with fundic atrophic gastritis after H. pylori eradication, which could be responsible for the increase or 'recovery' in acid secretion after the eradication.…”
Section: Referencesmentioning
confidence: 98%
“…Another article from Lithuania examined the relationship between H. pylori eradication in a cohort of duodenal ulcer patients and the development of erosive esophagitis (EE). EE developed in 8 of 70 (11.4%) successfully eradicated patients, in 9 of 49 (18.4%) unsuccessfully eradicated patients, and in 2 of 31 (6.5%) controls ( p > .05 comparing the groups), and the authors concluded that H. pylori eradication did not influence the incidence of EE over the 1‐year follow‐up period [37].…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%